1998
DOI: 10.1063/1.366743
|View full text |Cite
|
Sign up to set email alerts
|

Amphoteric native defect reactions in Si-doped GaAs

Abstract: Strong evidence for amphoteric native defect reactions is obtained by photoluminescence analysis of Si-doped GaAs samples (n≈1.5×1018 cm−3) annealed under different conditions. Annealing in excess As4 vapor creates a large concentration of Ga vacancies, making possible the transformation of this defect into an As vacancy and an As antisite defect. Similarly, As vacancies generated at high concentration during annealing under Ga-rich conditions are transformed into Ga vacancies and Ga antisite defects. Photolum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 33 publications
1
27
1
2
Order By: Relevance
“…Beyond an electron concentration of about 1 Â 10 18 cm À3 the former one vanishes completely. In contradiction to the results published so far [17][18][19][20][21], we assign the 0.95 eV band to the (V Ga Si Ga ) 2À and the 1.15 eV transition to the (Si Ga V Ga Si Ga ) À complex. Detailed arguments will be published elsewhere [34].…”
Section: Si-doped Gaas Grown From Stoichiometric Meltscontrasting
confidence: 81%
See 1 more Smart Citation
“…Beyond an electron concentration of about 1 Â 10 18 cm À3 the former one vanishes completely. In contradiction to the results published so far [17][18][19][20][21], we assign the 0.95 eV band to the (V Ga Si Ga ) 2À and the 1.15 eV transition to the (Si Ga V Ga Si Ga ) À complex. Detailed arguments will be published elsewhere [34].…”
Section: Si-doped Gaas Grown From Stoichiometric Meltscontrasting
confidence: 81%
“…Studies on the influence of boron on vacancy concentrations show that boron decreases the concentration of Ga vacancies (V Ga ) [15,16]. Isolated vacancies form (donor-V Ga ) complexes due to Coulomb interaction and its concentration relates to the intensity of luminescence bands at 0.95 and 1.15 eV [17][18][19][20][21]. In this study, we present experimental data on the dependence of the formation of these compensating (donor-V Ga ) complexes on Si doping.…”
Section: Introductionmentioning
confidence: 95%
“…The peak position was independent of the incident intensity, and the peak height was proportional to the incident intensity. Ky et al 24 reported a peak between 1.45 eV and 1.47 eV in Si-doped GaAs (n = 1-8 × 10 18 cm -3 ) at 80 K. If 11 meV is added to these energies to compensate for the difference in temperature and thus bandgap, 21 the peak positions are seen to correspond. Ky et al 24 attributed the peak to transitions of free electrons to Ga As antisite acceptor defects, with an ionization energy of 68-77 meV.…”
Section: Resultsmentioning
confidence: 87%
“…Six elementary native point defect species exist in GaAs: vacancies in the Ga sublattice (V Ga ), vacancies in the As sublattice (V As ), Ga self-interstitials, As selfinterstitials, and antisite defects formed by a Ga atom on an As site (Ga As ) or an As atom on Ga site (As Ga ). 19 Amongst the six intrinsic defects of GaAs, only V Ga and Ga As are acceptors. 20 For Si doped GaAs, it has been found that Si can behave as donor Si Ga , an acceptor Si As and form Si pairs, clusters and complexes of Si atoms with native defects 12 , which together can be responsible for self compensation mechanisms and creation of energy levels in the forbidden energy gap.…”
Section: Discussionmentioning
confidence: 99%